Teaching, research or balanced? An exploration of the experiences of biomedical scientists working in UK medical schools. Issue 11 (6th October 2021) - Collett, Tracey; Capey, Steve; Edwards, James; Evans, Darrell J.; McLachlan, John C.; Watson, Helen; Bristow, David
Abstract : Driven by demand for high standards in university education, efforts have been made in the UK to address the perceived imbalance between teaching and research. However, teaching is still perceived by many as having less credibility and is attributed less importance. The purpose of our research was to explore how distinct types of academic job profiles ('research' or 'education' focused, or 'balanced') impact on biomedical scientists' perceptions of the lecturer role. Specifically, we investigated the experiences of biomedical scientists in 'post‐1990' medical schools, which are known for their commitment to excellence in both research and education. We conducted 22 face‐to‐face, semi‐structured interviews with biomedical scientists in five schools. Focusing on experiences of work, the interviews covered: 'motivations', 'role expectations', 'teaching', 'research' and 'career'. The recorded qualitative data were transcribed and then analysed thematically. Our results, offering an insight into the working lives of biomedical scientists in medical education, suggest that in settings with a dual emphasis on education and research, individuals on 'balanced' contracts can experience a strong pull between research and teaching. In addition to posing significant challenges with respect to workload management, this can impact profoundly on professional identity. In contrast to the balanced role, 'research' or 'education' focused roles appear to have clearer requirements, leading to higher employee satisfaction. We conclude that to assist the educational mission of Higher Education, attention should be paid to balanced contracts, to (a) ensure employee support, (b) mitigate against negative perceptions of teaching, and ultimately, (c) guard against staff attrition. Abstract : This article, based on interviews with biomedical scientists, explores the experience of working in UK medical schools. As well as providing an insight into the everyday demands of lecturing, it considers three different contract types ('education' or 'research' focused or 'balanced') and asks 'what are the implications for education and research in settings that stress equal attention to both?'